2009
DOI: 10.1007/s00127-009-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Needs of Indian schizophrenia patients: an exploratory study from India

Abstract: Most of needs of schizophrenia patients are unmet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
9
31
0
5
Order By: Relevance
“…Most of the types of needs presented by the patients of this study are consistent with the findings of several other studies [5,7,910]. The average number of needs of these patients (as measured by 2-COM Checklist) was lower than the average shown by patients in European countries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most of the types of needs presented by the patients of this study are consistent with the findings of several other studies [5,7,910]. The average number of needs of these patients (as measured by 2-COM Checklist) was lower than the average shown by patients in European countries.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that these patients are more aware of their needs than those with a less favorable attitude toward medication, who are probably less adherent to drug treatment. In the same way and in the same direction as previous studies [9,14,57], other socio-demographic variables are related to patients’ needs. Patients with higher family income reported fewer needs regarding Money and Benefits and Treatment information.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Researchers studying ''unmet needs'' have found that people whose needs go unmet tend to be older (Hansson et al 1995;Middleboe et al 2001) and male (Kulhara et al 2010;Ochoa et al 2003); they have multiple mental disorders (Baksheev et al 2010;Hansson et al 1995), as well as cooccurring drug or alcohol abuse (Baksheev et al 2010;Tremblay et al 2014) They may also experience low quality of life (Bengtsson-Tops and Hansson 1999;Slade et al 2004;Van Busschbach and Wiersma 2002), little social support (Wiersma and van Busschbach 2001), and trouble functioning in the community (Ochoa et al 2003;Slade et al 1999). These patients also consult fewer professionals (Gallagher and Teesson 2000;Lasalvia et al 2000).…”
Section: Introductionmentioning
confidence: 94%
“…Deve-se salientar que o desemprego também costuma se mostrar associado aos transtornos mentais graves e, de alguma forma, representam a relação entre aderência ao tratamento e esse grupo de pacientes (Lerner et al,1993 ,0-7,8 (McCrone et al, 2001;Ochoa et al, 2005;Wennström & Wiesel, 2006;Arvidsson, 2008;Wiersma et al, 2009;Trauer, 2010). Em estudos de países de baixa e média renda, como o Brasil, a média de necessidades totais foi mais alta, de 6,1 a 8,7 (Yeh, Luh, Liu, Lee & Slade, 2006;Kulhara et al, 2010;Ernest et al, 2013, Zahid & Ohaeri, 2013.…”
Section: Aderência Ao Tratamento E Características Associadasunclassified